2014
DOI: 10.1103/physrevb.89.195135
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of uniaxial strained and bent ZnO wires

Abstract: We investigated the variation of the electronic band gap of ZnO bulk and that of bent ZnO nanowires under the influence of uniaxial strain by using density functional theory. By applying a strain of about ±2% to bulk ZnO in equilibrium, we mimic the recent experimentally determined tensile and compressive strain along the c axis of ZnO microwires which results from the bending of such wires. The slope of band gap size versus tensile-compressive strain at the equilibrium gives a deformation potential parameter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Previous a cc calculations are based on generalized gradient approximation (GGA) or projector augmented wave method (PAW), which are plotted in Figure 4b. When we calculate a cc from reported conduction band d i (i = 1, 2) and valence band C i (i = 1,2,…) deformation potentials [29][30][31][32][33] of Pikus-Bir strain Hamiltonian 31,46 for wurzite semiconductor (Γ 9v valence band symmetry), reported bulk ZnO Poisson ratio in c-axis 47 (ν c,Bulk = 0.32) is used.…”
Section: Factors Of a CC Value Scattering In Literature: Strain Gradimentioning
confidence: 99%
“…Previous a cc calculations are based on generalized gradient approximation (GGA) or projector augmented wave method (PAW), which are plotted in Figure 4b. When we calculate a cc from reported conduction band d i (i = 1, 2) and valence band C i (i = 1,2,…) deformation potentials [29][30][31][32][33] of Pikus-Bir strain Hamiltonian 31,46 for wurzite semiconductor (Γ 9v valence band symmetry), reported bulk ZnO Poisson ratio in c-axis 47 (ν c,Bulk = 0.32) is used.…”
Section: Factors Of a CC Value Scattering In Literature: Strain Gradimentioning
confidence: 99%
“…These values agree very well with those deduced from theoretical calculations, which yields D 1 ¼ À2:18 eV… À 4:14 eV and D 2 ¼ À6:7 eV… À19:2 eV, depending on the applied method. 19 From the difference between the linear deformation potential determined here and those reported previously by us with D 1 ¼ ðÀ2:0460:02Þ eV, 7 we attribute to fact that in the experiments presented here the shift of the entire near band gap emission peak was investigated whereas in our previous experiments we focus on the shift of the exciton line as a function of the strain.…”
mentioning
confidence: 52%
“…This behaviour is in agreement with theoretical calculations using local density approximation (LDA) and generalized gradient approximation. 19 For the determination of the optical deformation potential of the observed energy shift, we described the change of the emission energy by a polynomial of second order through zero, i.e.…”
mentioning
confidence: 99%
“…For example, it was shown that an axial twist could realize metal-toinsulator transition in carbon NTs (CNTs) [14,15] and graphene NRs (GNRs) [16][17][18]. On the other hand, in deformed ZnO [19,20] and other semiconductor NWs [21][22][23], their fundamental bandgaps could be also tuned to a great extent. Strain can also alter the architecture of the entire electronic spectrum of the system.…”
Section: Introductionmentioning
confidence: 99%